O impacto da oferta de crédito no investimento privado brasileiro - Smaniotto, Emanuelle Nava (Universidade do Vale do Rio dos Sinos, 2017)
This paper shows an analysis about the credit supply impact on private investment in Brazil, between 2001 and 2016. For this purpose, the Markovian Regime Change (MR-DR) methodology is introduce in order to capture the different cycles between Free Credit, Directed Credit and Private Investment. In addition, the Autoregressive Vectors (VAR / VEC) model is apply to analyze the causalities and impulse-response functions. It was possible to prove the positive impact of the credit series on private investment. Thus, is demonstrate the importance of directed credit concession for sustaining private investment levels in periods of economic instability. On another hand, an indication of the importance of macroeconomic policies in periods of instability, with an example to the post-crisis period of 2009, has been consolidated along with the literature, through intensification of Directed Resources, in order to sustain the levels aboutPrivate Investment (FBME) in country.
Keywords: Impacto; Crédito; Investimento; Vetores autorregressivos; Recursos direcionados; Impact; Credit; Investment; Autoregressive vectors; Targeted resources; ACCNPQ::Ciências Sociais Aplicadas::Economia